Regionalism and infrastructure development - MOON, Seon Ho (KDI School, 2017)
Improving connectivity through cross-border infrastructures plays a vital role in development. However, such cross-border infrastructures are largely undersupplied, especially in developing economies, as they are regional public goods (RPGs) that confront coordination failures among national governments. While appropriate interventions are necessary for optimal provision of RPGs, in the absence of supranational authority (‘anarchy’), such a role for regional cooperation is carried out by different regional actors and through different institutions (rules of the game). In the East African Community (EAC), regional cooperation for development is dominantly led by Kenya, a regional hegemon, while in the Greater Mekong Subregion (GMS), the process is essentially led by the support of the ADB. Both regional communities desperately strive to achieve economic development through high quality infrastructure and facilitation of trade. By scrutinizing the two selected regional communities, this paper aims to reveal the drivers behind the emergence of regionalism in the two regions and how they affect the dynamics of the provision of transport infrastructure. It will also seek for their implications for trade and economic development. In the course of analysis, international relations theories, political economy analysis (PEA), and descriptive statistics will be used to compare the two regions. The paper finds that due to absence of an effective coordinator and fragmented implementation of regional transport policies, balanced infrastructure development and growth in intra-regional trade have been relatively less successful in the EAC than in the GMS.
Thesis(Master) --KDI School:Master of Development Policy,2017